Eksperimentasi Pembelajaran Matematika Dengan Model IBL (Inquiry Based Learning) dan CMP (Connected Mathematics Project) Ditinjau dari Kemampuan Penalaran Matematis Siswa Kelas VIII SMP Negeri 1 Ngemplak - Shodiq, Annabi Nur; , Dra. Nining Setyaningsih. M, Si (2016)
This research aims to analyze the influence of the use of Inquiry learning model Based Learning and Connected Mathematics Project of learning achievements reviewed from the mathematical reasoning ability students. This research is experimental research treatment on learning model. The population in this research is by the students of class VIII SMP 1 Ngemplak 2015/2016 in 8 class. A sample of this research is determined by the technique of cluster random sampling so that it is obtained that the class VIII B as class experiments and class VIII A as control classes. The instrument used in the form of questionnaires mathematical reasoning ability and learning mathematics achievement test. The Data obtained were analyzed by using Anava two lines previously performed by using Liffefors normalitas test method and homogenitas test by using the Bartlett method. The results of the research with = 5% showed that: (1) there is a significant impact between the use of learning model IBL (Inquiry Based Learning and CMP (Connected Mathematics Project) toward students learning achievements, with FA= 11,678, (2) there is influence the mathematical reasoning ability students whether high, medium, or low toward the achievements of learning mathematics, with FB= 4,329, (3) there is no effect of the interaction between the learning model IBL (Inquiry Based Learning and CMP (Connected Mathematics Project) with the mathematical reasoning ability students to the learning achievements, with FAB= 2,594.